PENGARUH STRUKTUR MODAL, PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2011-2014) - Reza Noor Najma, 11.05.52.0159; Lisiantara, Greg Anggana (Students Journal of Accounting and Banking, 2016)
This study examinedthe analysis of the influence of thestructure of capital structure, profitability,company size, age companies and debt policy to the value of the company.The research was done in theIndonesia Stock Exchange(IDX)using manufacturing companygoing public. The purpose of thisstudy was to determine the effectofcapital structure, profitability,company size,and dividen payout ratio to the value of the company.in companies listed on theStockExchange during the study periode 2011-2014. The data obtainedfrom the financial statements ofpublicly traded companies at IDX. Thenumber of samples is 217 manufacturing company. Dataanalysis method used is multiplelinearregression analysis wasused to test the effect of two ormore variables between theindependent variables, namely the capital structure, profitability,company size,and dividen payout ratio to the value of the company of the companieslistedin Indonesia Stock Exchange(IDX ) as the dependent variable.The results showed individual profitability and firm size are significant positiveeffect on the 0value of the company, the dividen payout ratio is positive not significant of thevalue of the company, capital structure isnât significant negative effect on the value of the companyKeywords: capital structure, profitability,company size, and deviden payout to the value of the company.